Memórias inventadas e vividas em José Saramago: entre verdade e ficção - Rolim, Michelle de Oliveira (2009)
This work aims to identify traces of the author's autobiographical narrative Manual de pintura e caligrafia by José Saramago, constantly referring to the autobiography As pequenas memórias and to interviews that contribute to the elucidation of possible autobiographical influences of the author, inserted obliquely into the fiction. From these narratives, written in first speech, the issue of representing will be verified under the light of theories related to the theme of representation in writing, such as the works of Umberto Eco, Roland Barthes, Anatol Rosenfeld and Philippe Lejeune. Therefore it will be noticed that both autobiographical and fiction writings reveal a double foresight that the author creates from the world and from himself, developing inner versions that unfold in double autobiographies and alter egos, making thin lines between what are imagined memories and those actually lived. It is also addressed the importance of language in the process of the identity constitution of an individual that is nearly a complete black out. Everything leads to believe that, as in the romances, the memorialist texts also reveal the difficulties of representation, as the writing itself is a simplified and compact translation of the autobiographer.